2016
DOI: 10.1080/19440049.2016.1167965
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplement for energy and reduced appetite containing the β-agonist isopropyloctopamine leads to heart problems and hospitalisations

Abstract: In 2013 the Dutch authorities issued a warning against a dietary supplement that was linked to 11 reported adverse reactions, including heart problems and in one case even a cardiac arrest. In the UK a 20-year-old woman, said to have overdosed on this supplement, died. Since according to the label the product was a herbal mixture, initial LC-MS/MS analysis focused on the detection of plant toxins. Yohimbe alkaloids, which are not allowed to be present in herbal preparations according to Dutch legislation, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…This product was found to contain synephrine, methylsynephrine, isopropyloctopamine, and caffeine along with other components 40 . A study published later found 40–60 mg isopropyloctopamine per dose in the three batches of the suspect supplement analyzed 41 . In this study, the presence of phenylephrine or etilefrine was not detected in any of the analyzed products.…”
Section: Resultsmentioning
confidence: 38%
“…This product was found to contain synephrine, methylsynephrine, isopropyloctopamine, and caffeine along with other components 40 . A study published later found 40–60 mg isopropyloctopamine per dose in the three batches of the suspect supplement analyzed 41 . In this study, the presence of phenylephrine or etilefrine was not detected in any of the analyzed products.…”
Section: Resultsmentioning
confidence: 38%
“…Examples of UHPLC-QTOF-MS applications include quantification of yohimbine, synephrine, and oxilofrine [35,84,103,104], while QqQ was mostly used for analysis of synephrine and octopamine [105][106][107][108]. Orbitrap, on the other hand, was used for analysis of yohimbine [104,109], arecoline [110], and isopropyloctopamine [93]. LC with UV detection, either in form of a single-wavelength detection or PDA, was also used in several applications.…”
Section: Analytical Methods For Quantification Of Alkaloids and Phenymentioning
confidence: 99%
“…In the UK, a 20-year-old woman, said to have overdosed on this supplement, died. The levels of natural phenylethanolamines, although relatively high, could not explain the incidence of side effects, but the presence of isopropyloctopamine led to suspicion that isopropyloctop-amine was the compound responsible for most of the observed side effects [93]. A supplement containing synephrine, octopamine, tyramine, and caffeine caused coronary spasm and thrombosis in a bodybuilder [78], while a series of adverse effects caused by a supplement containing multiple active ingredients, including isopropyloctopamine, was described before [35].…”
Section: Octopamine and Isopropyloctopaminementioning
confidence: 99%
“…The use of effect-based screening has the advantage that, alongside the standard substances, new unknown substances and designer drugs can be detected (Van Ginkel & Sterk, 2016). They are also deployed for forensic research in areas beyond the scope of the NP (Bovee et al, 2016).…”
Section: Effect Based Assaysmentioning
confidence: 99%